Presenting a framework for knowledge management within a web-enabled Living Lab - Lizette de Jager; Albertus A.K. Buitendag; Jacobus S. van der Walt (South African Journal of Information Management, 2012)
Background: The background to this study showed that many communities, countries and continents are only now realising the importance of discovering innovative collaborative knowledge. Knowledge management (KM) enables organisations to retain tacit knowledge. It has many advantages, like competitiveness, retaining workers’ knowledge as corporate assets and assigning value to it. The value of knowledge can never depreciate. It can only grow and become more and more valuable because new knowledge is added continuously to existing knowledge. Objective: The objective of this study was to present a framework for KM processes and using social media tools in a Living Lab (LL) environment. Methods: In order to find a way to help organisations to retain tacit knowledge, the researchers conducted in-depth research. They used case studies and Grounded Theory (GT) to explore KM, social media tools and technologies as well as the LL environment. They emailed an online questionnaire and followed it up telephonically. The study targeted academic, support and administrative staff in higher education institutions nationwide to establish their level of KM knowledge, understanding of concepts and levels of application. Results: The researchers concluded that the participants did not know the term KM and therefore were not using KM. They only used information hubs, or general university systems, like Integrated Technology Software (ITS), to capture and store information. The researchers suggested including social media and managing them as tools to help CoPs to meet their knowledge requirements. Therefore, the researchers presented a framework that uses semantic technologies and the social media to address the problem. Conclusion: The success of the LL approach in developing new web-enabled LLs allows organisations to amalgamate various networks. The social media help organisations to gather, classify and verify knowledge.